Medical Management of Grey Slender Loris with Tonic Clonic Seizures – A Case Report - Navaz Shariff; H.V. Madhav (The Indian Veterinary Journal, 2026)
An adult male Slender Loris weighing 230 g was rescued, which was found recumbent on the ground. On observation and physical examination, it was noticed that the animal had tonic-clonic seizures every 30 mins and each episode lasted for 4-5 seconds. The animal was treated with inj. diazepam and oral homoeopathic medication. The animal was fed with a homemade feeding formula and glucose solution. The animal was observed for 36 hours after treatment, during which it showed no recurrence of seizures, and then it was released back into the wild.